Hubungan antara Disiplin Belajar dan Motivasi Belajar dengan Prestasi Siswa SMP Negeri 2 Kaloran Kabupaten Temanggung - Aang Ratnawati; Waluyo Waluyo; Sukhitta Dewi (STAB Maitreyawira, 2023)
The purpose of this study was to (1) determine a significant relationship between learning discipline and learning motivation with student achievement at SMP Negeri 2 Kaloran, Temanggung Regency, (2) find out a significant relationship between learning discipline and student achievement if learning motivation is controlled, (3) find out a significant relationship between learning motivation and student achievement if discipline is controlled. The background is that the learning discipline and learning motivation of students at SMP Negeri 2 Kaloran, Temanggung Regency is less than optimal. The research method used is correlational quantitative. The research sample was 116 students who were taken by simple random sampling. Collecting data using a questionnaire(questionnaire) to determine the discipline of learning and student motivation. The results showed (1) there was a significant relationship in the formation of student achievement at SMP Negeri 2 Kaloran, Temanggung Regency through learning discipline andlearning motivation. This is indicated by the value of sig. 0.00 < 0.05, (2) there is a significant relationship between learning discipline and student achievement at SMP Negeri 2 Kaloran, Temanggung Regency if learning motivation is controlled, indicated by a correlation coefficient of 0.417 with a variable contribution of 66.38% being in very high criteria, (3) there is a significant relationship between learning motivation and student achievement at SMP Negeri 2 Kaloran, Temanggung Regency if learning discipline is controlled, indicated by a correlation coefficient of 0.689 with a variable contribution of 35.34% being in high criteria.